2018
DOI: 10.12988/ces.2018.810536
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the theoretical stress concentration factor in structural flat plates with two holes subjected to bending loads

Abstract: Numerous research works have studied the stress distribution in sections with geometric discontinuities and the relationship with the theoretical factor of stress concentration using the finite element method. These works have dealt with topics such as the influence of the length of pieces on the factor in rectangular orthotropic plates; The behavior of the stress concentration factor on short shafts with section changes under bending loads; The theoretical factor of stress concentration in flat parts subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ali Bilek et al experimented with a two-dimensional photoelasticity test (Plane Polariscope) on a plate that was loaded on its edge by a rigid steel cylinder [70]. C. A. Penaloza et al have utilized FEA for found stresses generated in orthotropic plates having circular holes under bending, which shows stress concentration was increasing as the spacing of holes decreased [73]. Under the transverse loading, the effect of the circular hole on stress concentration factor in isotropic square simply supported plate was obtained by M. Banerjee et al They have used three dimensional photo elastic methods and FEA method which shows variation between −2.66% to 4.44% [74].…”
Section: According To Types Of Loadingmentioning
confidence: 99%
“…Ali Bilek et al experimented with a two-dimensional photoelasticity test (Plane Polariscope) on a plate that was loaded on its edge by a rigid steel cylinder [70]. C. A. Penaloza et al have utilized FEA for found stresses generated in orthotropic plates having circular holes under bending, which shows stress concentration was increasing as the spacing of holes decreased [73]. Under the transverse loading, the effect of the circular hole on stress concentration factor in isotropic square simply supported plate was obtained by M. Banerjee et al They have used three dimensional photo elastic methods and FEA method which shows variation between −2.66% to 4.44% [74].…”
Section: According To Types Of Loadingmentioning
confidence: 99%